Characteristics of Instant Baby Porridge With a Pre-Cooked Flour Formulation (White Rice, Yellow Corn, Red Beans and Snakehead Fish) - Aina, Untsa Qurrota; Rosida, Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Stunting prevention can be done by providing Complementary Foods (MP-ASI) to babies aged 6 months and above. Baby porridge is generally made from rice, to increase the nutritional content of instant baby porridge, yellow corn is substituted. Red beans and snakehead fish have high protein content to increase the nutrition of instant baby porridge. The pre-cooking process on flour needs to be done to increase water absorption and solubility in instant baby porridge products. The purpose of this study was to determine the effect of differences in pre-cooked flour formulations (white rice, yellow corn, red beans and snakehead fish) on the physicochemical and organoleptic characteristics of instant baby porridge. The study used a simple Completely Randomized Design (CRD) with one factor, with treatments P1, P2, P3, P4, P5 and P6. Data analysis using ANOVA and further testing of 5% DMRT was carried out if there was a significant difference. Instant baby porridge with pre-cooked flour formulation P3, with a water content of 3.66%, ash content of 2.91%, fat content of 11.88%, protein content of 21.64%, carbohydrate content of 59.88%, starch content of 28.41%, crude fiber content of 2.80%, bulk density of 0.49 g/ml, water absorption capacity of 222.75%, solubility of 28.88%, and organoleptic test of color 3.44 (neutral), aroma 3.36 (neutral), taste 3.64 (like), and texture 3.76 (like).